Leptin alleviates endoplasmic reticulum stress induced by cerebral ischemia/reperfusion injury via the PI3K/Akt signaling pathway. Issue 12 (12th December 2022) - Zhang, Yan; Cheng, Daobin; Jie, Chunxiao; Liu, Tao; Huang, Shixiong; Hu, Shijun
Abstract: Background: Cerebral ischemic/reperfusion injury (CIRI) is a key factor for the prognosis of ischemic stroke (IS), the leading disease in terms of global disability and fatality rates. Recent studies have shown that endoplasmic reticulum stress (ERS) may be a target against CIRI and that leptin, a peptide hormone, has neuroprotective activity to mitigate CIRI. Methods : An in vitro CIRI model was induced in primary cortical neurons by oxygen-glucose deprivation and reoxygenation (OGD/R) after pretreatment with LY294002 (10 µmol/L) and/or leptin (0.4 mg/L), and cell viability, neuronal morphology and endoplasmic reticulum (ER) dysfunction were evaluated. An in vivo CIRI model was established in rats by middle cerebral artery occlusion and reperfusion (MCAO/R) after the injection of LY294002 (10 μmol/L) and/or leptin (1 mg/kg), and neurological function, infarct volume, cerebral pathological changes, the expression of ERS-related proteins and cell apoptosis were examined. Results: In vitro, leptin treatment improved the cell survival rate, ameliorated neuronal pathological morphology and alleviated OGD/R-induced ERS. In vivo, administration of leptin significantly reduced the infarct volume, neurological deficit scores and neuronal apoptosis as well as pathological alterations. In addition, leptin suppressed MCAO/R-induced ERS and may decrease apoptosis by inhibiting ERS-related death and caspase 3 activation. It also regulated expression of the antiapoptotic protein Bcl-2 and the proapoptotic protein Bax in the cortex. Furthermore, the inhibitory effect of leptin on ERS was significantly decreased by the effective phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002. Conclusions: These results confirm that ERS plays an important role in CIRI and that leptin can inhibit the activation of ERS through the PI3K/Akt pathway, thereby alleviating CIRI. These findings provide novel therapeutic targets for IS.